Improving the detection rate of vancomycin-resistant enterococci colonisation using groin swabs. Issue 6 (17th March 2014) - Mahida, Nikunj; Boswell, Tim
Abstract : Vancomycin-resistant enterococci (VRE) are nosocomial pathogens associated with significant morbidity in immunosuppressed patients. Stool culture is considered the gold standard for VRE screening. However, in a clinical environment, there are difficulties associated with the practicalities of obtaining stool samples. Groin swabs, routinely collected as part of the mandatory admissions policy for meticillin-resistant Staphylococcus aureus screening were used to detect VRE. In direct comparison, stool culture had better sensitivity to groin swabs. However, groin swabs with broth enrichment allowed earlier detection of VRE carriage in 14 patients from whom stool samples could not be obtained in a timely manner.